2014
DOI: 10.1002/qj.2286
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an aerosol–cloud‐microphysics–radiation coupling into the NASA unified WRF: Simulation results for the 6–7 August 2006 AMMA special observing period

Abstract: Aerosols affect the Earth's radiation balance directly and cloud microphysical processes indirectly via the activation of cloud condensation and ice nuclei. These two effects have often been considered separately and independently, hence the need to assess their combined impact given the differing nature of their effects on convective clouds. To study both effects, an aerosol-microphysics-radiation coupling, including Goddard microphysics and radiation schemes, was implemented into the NASA Unified Weather Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 87 publications
5
65
1
Order By: Relevance
“…The cloud-to-rain auto-conversion is then calculated as a function of water content using a threshold approach, and the IN is used for calculation of the cloud ice mass. Aerosol mass concentrations for black carbon, organic carbon, sulfate, sea-salt, and dust are employed to calculate aerosol optical depth (AOD), single-scattering albedo, and asymmetry factor, which serve as inputs to a radiative transfer model to simulate aerosol interactions with radiation [28].…”
Section: Nu-wrf Modeling System Set-up and Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloud-to-rain auto-conversion is then calculated as a function of water content using a threshold approach, and the IN is used for calculation of the cloud ice mass. Aerosol mass concentrations for black carbon, organic carbon, sulfate, sea-salt, and dust are employed to calculate aerosol optical depth (AOD), single-scattering albedo, and asymmetry factor, which serve as inputs to a radiative transfer model to simulate aerosol interactions with radiation [28].…”
Section: Nu-wrf Modeling System Set-up and Experiments Designmentioning
confidence: 99%
“…The higher ozone (>45 ppbv) was modeled over the scatter areas in California, Arizona, Utah, Virginia, and North Carolina. Previous studies have shown that NU-WRF has sufficient skills in simulating land-atmosphere exchange, aerosol-cloud-radiation interactions, atmospheric photochemical processes, and air quality [21][22][23]28]. In this study, we compared the daily precipitation from the control experiment to the rain gauge data analyzed by the Climate Prediction Center of the National Oceanic and Atmospheric Administration under its unified precipitation project [45,46].…”
Section: Control Experiments (Noacr or F0) And Model Evaluationmentioning
confidence: 99%
“…This manuscript utilizes the NU-WRF simulation from Shi et al [2013] that features a specific Mesoscale Convective System (MCS) interacting with land and aerosols (mineral dust) processes over West Africa coincide with the African Monsoon Multidisciplinary Analyses (AMMA) experiments. As a demonstration of the radiance-based evaluation method, we primarily focus on the simulation results at 01 Z 6 August 2006, because of the maturity of the simulated MCS surrounded by mineral dust and the coinciding of these features with various satellite observations.…”
Section: Modeling Systemsmentioning
confidence: 99%
“…The third approach is used in most global or coarseresolution regional models for studies of aerosol-cloud interactions, even on a climatic scale (e.g., Storelvmo et al 2006Storelvmo et al , 2008Lohmann et al 2007;Morrison and Gettelman 2008;Suzuki et al 2008;Takemura et al 2009;Wang et al 2011;Wang et al 2013;Park et al 2014;Shi et al 2014). Supersaturation and the vertical wind velocity cannot be resolved well on model grid points with coarse intervals.…”
Section: Modeling Approaches To Aerosol and Its Activation In Dropletmentioning
confidence: 99%
“…Cloud-ice nucleation and heterogeneous freezing of supercooled droplets were calculated using the parametrizations of Bigg (1953), Koop et al (2000), Phillips et al (2008), andDeMott et al (2010). Shi et al (2014) used aerosol and chemical-transport model simulations as a tool to provide a realistically diagnosed aerosol field for their cloud microphysics calculation in the main model framework with the same domain configuration. They incorporated the following two individual models off-line: the GOCART solomodule version of the WRF coupled with chemistry (WRF-Chem; Grell et al 2005), and the National Aeronautics and Space Administration (NASA) Unified WRF (NU-WRF; Peters-Lidard et al 2015).…”
Section: Solutions To the Problem Related To Aerosol-to-cloud Modelingmentioning
confidence: 99%